2014 Electrical Energy Measurement Interlaboratory Comparison - Magaña-Godoy, Saúl (2017)
This paper presents the results of an Electrical Energy Measurements Interlaboratory Comparison, conducted in Costa Rica and Panamá in 2014, by the Instituto Costarricense de Electricidad (ICE)-Laboratorio Metrológico de Variables Eléctricas (LMVE) as a designated NMI in Costa Rica for Electricity, Magnetism, Time and Frequency. The comparison involved six participating laboratories from Costa Rica, the NMI of Panama CENAMEP AIP.